Borehole-image-log characterization of deltaic deposits from a behind-outcrop well: Opportunities and limitations - WOLPERT, P.J. (SEPM Society for Sedimentary Geology, 2019)
Borehole imaging (BHI) is a fast and precise method for collecting subsurface data. Rock calibration may reduce uncertainties inherent in interpretations of BHI logs. However, only few data sets are published that link borehole image facies to core and outcrop facies of deltaic successions. The objective of this paper is to compare and contrast sedimentologic features as seen in BHI, core, and outcrop, using a structured and hierarchical workflow. The research will provide a global framework for the interpretation of borehole images in similar environments. A shallow, behind outcrop, research well ("Mondot-1") drilled in NW Spain, penetrated a 185.50 m (TVD) thick section of the deltaic Sobrarbe Formation. A Formation MicroImager (FMI) borehole image log and a comprehensive well log suite was acquired in the fully cored well. The Eocene Sobrarbe Formation consists mostly of siliciclastic and some carbonate facies. Rapid vertical and lateral facies changes over a few tens of meters are observed in outcrops of the Sobrarbe Formation. The cored part of the formation is composed of argillaceous sandstone and carbonate with few diagnostic sedimentary features that can be used to constrain a conceptual depositional model. To provide a sedimentologically sound interpretation of this FMI log, we focused on layers showing diagnostic sedimentary features. Subsequently, facies associations and stratigraphic sequences were interpreted. Each facies association contained sedimentologic tie points that anchored the interpretation with diagnostic features such as slumps. This paper suggests interpreting BHI false-color images of deltaic successions using conceptual geologic constraints such as 1) depositional tie points, 2) genetically related facies associations, and 3) a hierarchical stratigraphic framework, to establish meaningful conceptual depositional models. Â© 2019, SEPM (Society for Sedimentary Geology).